A pan-cancer analysis: predictive role of ZNF32 in cancer prognosis and immunotherapy response - Minghan Li; Chang Su; Qianru Wang; Yuetong Chen; Di Jiang; Weijia Wang; Shunjin Chen; Xiangping Li; Ming Fu; Juan Lu (Discover Oncology)
Abstract The zinc finger protein 32 (ZNF32) has been associated with high expression in various cancers, underscoring its significant function in both cancer biology and immune response. To further elucidate the biological role of ZNF32 and identify potential immunotherapy targets in cancer, we conducted an in-depth analysis of ZNF32. We comprehensively investigated the expression of ZNF32 across tumors using diverse databases, including TCGA, CCLE, TIMER2.0, KM-Plotter, cBioPortal, ImmuCellAI. We investigated correlations between ZNF32 expression and various factors such as prognosis, immune infiltration, immunotherapy, DNA methylation, and biological functions. Furthermore, we performed in vitro research to validate the significance of ZNF32 in head and neck cancer (HNSC). Our study revealed that ZNF32 was high in various types of cancer, including ACC, BRCA, and others, indicating its important potential as a prognostic biomarker. Significant changes in CNA and DNA methylation were associated with high ZNF32 expression. ZNF32 was notably linked to various immune characteristics, including immune cell infiltration, MSI, TMB and immune checkpoint gene expression, indicating its potential in informing immunotherapy approaches. Interestingly, in FaDu and CAL27 cell lines, the group with elevated ZNF32 expression exhibited increased levels of immune checkpoint markers, such as CTLA-4 and PD-L1. Overexpression of ZNF32 significantly enhanced proliferation and migration in FaDu and CAL27 cell lines, as demonstrated through CCK-8 assays, colony formation, flow cytometry, Transwell migration, and Boyden invasion assays. Our in vitro experiments confirmed that ZNF32 promotes malignant behavior by driving HNSC cell proliferation and migration. These results imply that ZNF32 might be a promising target for tumor prognosis and immunotherapy. Our results highlight the important role of ZNF32 in tumorigenesis and provide novel perspectives for potential cancer treatment strategies.